PENGARUH FREE CASH FLOW, LEVERAGE, KOMPOSISI DEWAN KOMISARIS DAN KEPEMILIKAN INSTITUSIONAL TERHADAP MANAJEMEN LABA (Studi pada Perusahaan Perbankan yang Go Public di Bursa Efek Indonesia) - Cahyani, Wahyu Budi; Alliyah, Siti (JAB (Jurnal Akuntansi & Bisnis), 2019)
This study aims to examine the effect of free cash flow, leverage, the composition of the board of commissioners and institutional ownership on earnings management. The sample used in this study is a banking company listed on the Indonesia Stock Exchange for the period 2015-2017. Sampling uses a purposive sampling method. Obtained the number of samples in this study as many as 20 companies over 3 (three) years, so the number of observations is 60 and testing using multiple linear regression. The results showed that free cash flow had a significant negative effect on earnings management, leverage had a significant positive effect on earnings management, and the composition of the board of commissioners and institutional ownership had a non-significant negative effect on earnings management. Determination test results show that free cash flow, leverage, the composition of the board of commissioners and institutional ownership which is an independent variable is able to explain earnings management as the dependent variable by 20.8%, while the remaining 79.2% is influenced by other factors outside the model research that was not examined in this study. Keyword : Free Cash Flow, Leverage, Board of Commissioners Composition, Institutional Ownership, Profit Management